An Experimental Study of Think Pair Share (TPS) to Improve Writing Skill - Mega Wulandari; Agnes Rini (Journal of Language and Health, 2020)
Writing skill becomes one of the most important skills because it communicates students’ ideas and perception in written form. However, based on researcher’s observation, writing activity is not always successfully studied among the students because its complexity and challenges can be daunting for students. Writing should be learned with appropriate learning strategy. One of the techniques is called Think Pair Share (TPS) learning strategy was applied to improve students’ writing skills in class. According to Engkos Kosasih (2014), “Success in learning the materials is not only calculated by individual's ability but also working together in group” (p. 101). The goal of this study is to answer two research questions: (1) Does TPS improve the student’s writing skill in class XI IPS of SMA BOPKRI 2 Yogyakarta? (2) What are the students’ responses toward TPS in improving their writing skill in class XI IPS of SMA BOPKRI 2 Yogyakarta? The result of this study revealed that TPS learning strategy did improve their writing skills because it triggered positive changes in their learning attitude. They were encouraged to be more active, critical, and creative.